Proposta para adensamento arbóreo da área central e bairro Ronda em Ponta Grossa, PR, Brasil - Denny Wilson Jobbins Haas; Silvia Méri Carvalho (Terr@ Plural)
Afforestation of public roads provides social, environmental, and economic benefits. Keeping this in mind, the Public Ministry of Paraná determined that the state municipalities must prepare a Municipal Plan for Urban Afforestation. This article presents potential roads that can receive tree densification in the central area and in the Ronda neighborhood of Ponta Grossa, Paraná. Based on a methodology that considers adequate spacing among trees and urban components, it was possible to indicate which roads can receive more trees, which have the ideal number of trees, and which have more trees than expected. In this way, it was possible to perceive that, in the central area, 23 roads, over 65 blocks, can have an increase in tree densification, being able to receive up to 305 trees, while, in the Ronda neighborhood, the densification can occur on 25 roads, over 77 blocks, being able to receive up to 390 trees